Preparation and validation of the instrument “QualiAPS digital—Brazil” for assessing digital health care in primary health care: a required tool - de Figueirêdo, Renan Cabral; de Siqueira Silva, Ísis; de Araújo, Aguinaldo José; Silva, Cícera Renata Diniz Vieira; Martiniano, Cláudia Santos; Brito, Ewerton William Gomes; Xavier, Pedro Bezerra; da Costa Uchôa, Severina Alice (Frontiers in Public Health, 2024)
The use of Information and Communication Technologies in the field of health is increasing across the world, demarcating the field of digital health. The goal of this study is to formulate and validate a matrix of indicators, design assessment scripts and indicate data collection techniques for assessing the quality of digital health care in Brazilian Primary Health Care (PHC). Methodology: This is a validation study divided into three phases: preparation of the instrument, analysis of validity and pilot study. The instrument was prepared based on the PHC assessment model from a literature review; the analysis of validity used the Delphi technique associated with the nominal group and the evidence from the literature reference. In the pilot study, audio-recorded interviews were conducted with strategic primary care actors. Results: The matrix of indicators "QualiAPS Digital -Brazil" introduces a set of 37 indicators, distributed into three distinct components and their respective dimensions. The component "Structure" includes the dimension "Resources"; the component "Processes" includes the dimensions "Technical", "Organizational" and "Relational"; and the component "Results" includes the dimensions "Short-Term Results" and "Medium-Term Results". The general values obtained for CVI and IRR were 0.89 and 1.00; respectively. Therefore, it was possible to design assessment scripts and indicate qualitative data collection techniques for assessing digital health in Brazilian PHC. Conclusion: The instrument presented was validated regarding its relevance, content and theoretical support to evaluate the quality of digital health care, supporting decisionmaking by managers and health professionals in the search for improving remote primary care provided to the population.